Quality of Life Among Old Age Homes Residents in Gujarat, India: Evidence from a Sequential Explanatory Mixed Method Study - Mamta Roshan Patel; Uday Shankar Singh (National Journal of Community Medicine)
Introduction: The concept of old age homes is developing in India. For many elderlies, moving into old age homes becomes their only viable choice. Objectives: To assess the quality of life of the elderly living in old age homes and to explore stakeholders' perspectives on running these facilities.